2017
DOI: 10.1002/ejoc.201601580
|View full text |Cite
|
Sign up to set email alerts
|

Insights into the Scholl Coupling Reaction: A Key Transformation of Relevance to the Synthesis of Graphenes and Related Systems

Abstract: The Scholl‐type reactions of 4,10‐disubstituted chrysene derivatives proceeded by variegated and unexpected oxidation/coupling pathways. These observations serve as a cautionary note when attempting to employ the Scholl reaction in target‐oriented materials synthesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 95 publications
0
9
0
2
Order By: Relevance
“…To the best of our knowledge,t his represents the largest PA Hc ontaining at least two formal azulene units.B ased on our research on diarenoperylenes, [19] we recently found that Scholl-type oxidations of 1a and 1b with both FeCl 3 in nitromethane as well as with DDQ and trifluoromethanesulfonic acid gave five-membered ringcyclized products 2a and 2b exclusively. [20,21] We envisioned combining this highly selective Scholl-type reaction in amanner that would generate an additional seven-membered ring (Scheme 1), [22] preferably in the same step,r esulting in azulene formation during Scholl-cyclization, something that has previously only been observed on Au(111) surfaces. [16a] Accordingly,w es ynthesized the bisnaphthyl diareno precursor 3 from the corresponding bromide 6 [19b] by Suzuki-Miyaura cross-coupling in 67 %y ield (Scheme 2).…”
mentioning
confidence: 99%
“…To the best of our knowledge,t his represents the largest PA Hc ontaining at least two formal azulene units.B ased on our research on diarenoperylenes, [19] we recently found that Scholl-type oxidations of 1a and 1b with both FeCl 3 in nitromethane as well as with DDQ and trifluoromethanesulfonic acid gave five-membered ringcyclized products 2a and 2b exclusively. [20,21] We envisioned combining this highly selective Scholl-type reaction in amanner that would generate an additional seven-membered ring (Scheme 1), [22] preferably in the same step,r esulting in azulene formation during Scholl-cyclization, something that has previously only been observed on Au(111) surfaces. [16a] Accordingly,w es ynthesized the bisnaphthyl diareno precursor 3 from the corresponding bromide 6 [19b] by Suzuki-Miyaura cross-coupling in 67 %y ield (Scheme 2).…”
mentioning
confidence: 99%
“…Es überrascht nicht, dass sich die Scholl-Reaktion als besonders nützlich für die Bildung mehrerer kondensierter Ringe erwiesen hat, um polyzyklische Arene und Nanographenverbindungen zu erhalten. [5][6][7][8][9] Der Schritt der C-H-Aktivierung/ Arylierung bei der Synthese polyzyklischer aromatischer Kohlenwasserstoffe (PAK) ist jedoch im Allgemeinen nicht sehr selektiv, da die C-H-Bindungen nicht nur eine geringe intrinsische Reaktivität aufweisen, sondern auch nur geringe relative Unterschiede in ihrer Reaktivität. [9,10] Ergänzend zur etablierten Scholl-Reaktion in Lösung zeigt der analoge, oberflächenunterstützte C-C-Kopplungsprozess eine erstaunliche Effizienz bei der Herstellung von Nanographenund anderen Strukturen im atomaren Maßstab.…”
Section: Die Dehydrierende Kupplungsreaktion Zweier Arenringeunclassified
“…Special attention has been paid to materials chemistry, indicating that the discussed cycloadditions, especially combined with another novel synthetic tool, constitute a powerful and versatile tool for materials chemistry. Of particular importance in the aforementioned combination of different reactions is Scholl dehydrocondensation allowing π-expansion from DA cycloaddition (and other types of cycloaddition and coupling reactions) products [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Particular attention is paid to nanographenes, including functionalized and heteroatoms-doped ones, which preparation and new applications constitute a “hot topic” in science and technology [ 6 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 ]. Currently, only bottom-up methods, where nanographene is constructed from smaller entities by stepwise organic synthesis, allow the preparation of nanographenes, including functionalized and doped ones, with perfect control of shapes and sizes and, therefore, perfectly defined properties [ 2 , 5 , 6 , 11 , 12 , 14 ,…”
Section: Introductionmentioning
confidence: 99%